Evaluation of adjuvants in fungicide spray application for the control of alternaria brown spot in South African citrus orchards - Van Zyl, Johannes Gideon (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.